Accelerating change in schools : leading rapid, successful, and complex change initiatives - Dudar, Linda; Scott, Shelleyann; Scott, Donald E. (Bingley : Emerald Publishing Limited, 2017)
Research indicates change is complex and difficult, and requires considerable time to achieve, sometimes years or even decades. This book presents major findings from a research study exploring the leadership needed to enact rapid change - defined as three years or less - in various school contexts, overtly including the perspectives of leaders, teachers, students, parents, community members, and district leaders. We challenge many of the assumptions in current scholarly literature about how fast, complex change can or should be wrought within educational environments; indeed, our premise is that rapid, complex change is not only possible but may be highly desirable and successful given the right leadership approach.We present a pragmatic'rapid change' model emerging from in-depth explorations of successful leadership approaches that accelerated the change agenda in these schools. We outline the theoretical underpinnings to the model and overtly articulate the pragmatic approaches leaders found to be effective in implementing fast-paced change. We also present case studies of successful change in schools with descriptions and advice elicited from leaders and stakeholders.
Prelims -- Section I - Leadership and rapid change -- The demand for rapid change -- Understanding the theory of change processes -- Stakeholders and change participants - Important influencers -- Defining change leadership -- The self-aware and discerning change agent -- The rapid change model -- Section II - Rapid change: success stories from educational leaders -- The head and heart of change: leaders' advice about change -- Leaders' success stories of culture (people) change -- Leaders' success stories of program change -- Stakeholders are important too! -- Context is interesting and important -- Are you ready? -- About the Authors -- References -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Education -- Administration -- General; Education; Educational leadership